2021
DOI: 10.25115/ejrep.v19i54.4037
|View full text |Cite
|
Sign up to set email alerts
|

Variables que predicen la participación en los dispositivos de apoyos académicos institucionales (AAI)

Abstract: Introducción: Ante la necesidad de focalizar los esfuerzos para que los estudiantes que más lo requieran puedan ser parte de los apoyos académicos que brindan las instituciones universitarias, se realizó un estudio para identificar las variables que mejor predicen la participación voluntaria en estos dispositivos. Método: Participaron en este estudio 803 estudiantes universitarios de ambos sexos de cuatro universidades chilenas. El instrumento midió variables de carácter personal y condicionantes relacionadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Nursing students Quantitative Results indicated that students have a positive attitude towards academic help-seeking, and educators should address the factors that hinder it. Help-seeking is a useful strategy that benefits academic success 32 48 Valenzuela [ 106 ] (2021) Chile Variables Predicting Participation in institutional academic support services (IAS) To identify the variables that best predict voluntary participation in these services 803 male and female university students from four Chilean universities participated in this study Quantitative Results indicated that predictors of participation in institutional academic support services include awareness of need, knowledge of procedures, experience seeking help, and cost associated with loss of alternatives 38 49 Vilkova [ 88 ] (2021) Russia Deconstructing self-regulated learning in MOOCs: In search of help-seeking mechanisms To fill the gap in understanding the structure of SRL skills utilizing the Online Self-Regulated Learning Questionnaire (OSLQ) 913 Russian MOOC learners Quantitative Results indicated that the dimension ‘help-seeking’ is not effective in the MOOC environment 37 50 Williams-Dobosz [ 107 ] (2021) United States Ask for help: Online help-seeking and help-giving as indicators of cognitive and social presence for students underrepresented in chemistry To analyze help-seeking behaviors and responses to requests for help in an online college-level chemistry course’s discussion forum 94 students enrolled in and completed an online, asynchronous, early curriculum, college-level chemistry course Quantitative Results indicated that requests for help were responded to equally, regardless of how explicitly students appealed for help 36 …”
Section: Table A1mentioning
confidence: 99%
“…Nursing students Quantitative Results indicated that students have a positive attitude towards academic help-seeking, and educators should address the factors that hinder it. Help-seeking is a useful strategy that benefits academic success 32 48 Valenzuela [ 106 ] (2021) Chile Variables Predicting Participation in institutional academic support services (IAS) To identify the variables that best predict voluntary participation in these services 803 male and female university students from four Chilean universities participated in this study Quantitative Results indicated that predictors of participation in institutional academic support services include awareness of need, knowledge of procedures, experience seeking help, and cost associated with loss of alternatives 38 49 Vilkova [ 88 ] (2021) Russia Deconstructing self-regulated learning in MOOCs: In search of help-seeking mechanisms To fill the gap in understanding the structure of SRL skills utilizing the Online Self-Regulated Learning Questionnaire (OSLQ) 913 Russian MOOC learners Quantitative Results indicated that the dimension ‘help-seeking’ is not effective in the MOOC environment 37 50 Williams-Dobosz [ 107 ] (2021) United States Ask for help: Online help-seeking and help-giving as indicators of cognitive and social presence for students underrepresented in chemistry To analyze help-seeking behaviors and responses to requests for help in an online college-level chemistry course’s discussion forum 94 students enrolled in and completed an online, asynchronous, early curriculum, college-level chemistry course Quantitative Results indicated that requests for help were responded to equally, regardless of how explicitly students appealed for help 36 …”
Section: Table A1mentioning
confidence: 99%